Three-point bending properties of 3D_C/C_TiC_Cu composites based on acoustic emission technology. (1st February 2023) - Wang, Xianghong; Xie, Hong; Tong, Yonggang; Wang, Bin; Hu, Hongwei
Abstract: Ceramic matrix composites with three-dimensional (3D) braided structures have been become one of the research hotspots owing to their excellent properties such as high strength and high-temperature resistance. In this study, acoustic emission (AE) as a non-destructive technique was utilised to monitor the three-point bending process of 3D_C/C_TiC_Cu composites and investigate the damage change of the materials under different bending stress. Firstly, the sentry function is used to divide the damage stages. Then the acoustic feature parameters are used to evaluate the damage condition. Finally, the time–frequency characteristics of damage signals are compared to verify the damage type of the composites at different stages. The results demonstrate that the sentry function can effectively distinguish the four stages of the damage process: the initial damage stage, the damage developing stage, the rapid damage stage and the failure stage. By analysing the acoustic feature parameters and time–frequency characteristics of the signals, the damage mechanism and the damage state of the composites can be obtained qualitatively. Consequently, the AE technique is an effective tool for evaluating damage evolution of 3D_C/C_TiC_Cu composites.